2004
DOI: 10.1021/jm030346v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Flexible Sulfur-Containing Heteroarotinoids That Induce Apoptosis and Reactive Oxygen Species with Discrimination between Malignant and Benign Cells

Abstract: Regulation of growth, differentiation, and apoptosis by synthetic retinoids can occur through mechanisms that are dependent and independent of their ability to bind and activate nuclear retinoic acid receptors. The objective of this study was to determine if increasing flexibility of the heteroarotinoid structure would affect the specificity of the synthetic retinoids for the receptors and for their regulation of cancerous and nonmalignant cells. Methods were developed to produce the first examples of heteroar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
106
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(114 citation statements)
references
References 31 publications
(71 reference statements)
7
106
0
1
Order By: Relevance
“…The mechanism of this activity has been shown to occur through the intrinsic mitochondrial pathway associated with loss of mitochondrial membrane integrity, generation of reactive oxygen species (ROS), release of cytochrome c from mitochondria, and activation of caspase-3 in head and neck cancer cell lines (4). Generation of ROS was confirmed in ovarian cancer cell lines (2).…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…The mechanism of this activity has been shown to occur through the intrinsic mitochondrial pathway associated with loss of mitochondrial membrane integrity, generation of reactive oxygen species (ROS), release of cytochrome c from mitochondria, and activation of caspase-3 in head and neck cancer cell lines (4). Generation of ROS was confirmed in ovarian cancer cell lines (2).…”
Section: Introductionmentioning
confidence: 87%
“…Role of ROS in the Flex-Het Mechanism Our previous studies showed that SHetA2 induces ROS in ovarian and in head and neck cancer cell lines (2,4). To test the hypothesis that SHetA2 exerts mitochondrial effects through generation of intracellular ROS, the ability of SHetA2 to induce apoptosis in the presence of the antioxidants BHA or MnTBAP was measured.…”
Section: Differential Effects Of Flex-hets On Mitochondria In Cancer mentioning
confidence: 99%
See 3 more Smart Citations